You’re not alone: imagery rescripting for adolescents who self-harm - Schmied, Elisa; Hack, Lisa; Connemann, Bernhard; Sosic-Vasic, Zrinka; Kroener, Julia (Frontiers in Psychology, 2024)
Introduction: Non-suicidal self-injury (NSSI), which refers to the deliberate act of causing harm to one's own body without the intent to commit suicide, occurs in 20% of youth. Interestingly, approximately 90% of individuals who engage in self-harm report intrusive mental imagery thereof shortly prior to the act of NSSI. Previous research has demonstrated that imagery rescripting (IR) is an effective technique to treat intrusive mental images and associated clinical symptoms, such as emotion dysregulation, in various psychiatric disorders. However, there is no research on IR for adolescents who self-harm. Therefore, the present study aims to investigate the efficacy and feasibility of a two-session short-intervention using IR to reduce NSSI and associated clinical symptoms in adolescents. The intervention was supported by an app-based digital health intervention (DHI). Methods: A single case series A-B design with three post-assessments (one week, one month, and three months post-intervention) was implemented. Seven adolescents received two treatment sessions of IR, supported by a DHI between sessions. NSSI (SITBI), emotion regulation (ERQ), emotional distress (BDI-II, STAI-T), self-efficacy (WIRKALL_r), and treatment satisfaction (BIKEP) were evaluated. Results: There was an increase in adaptive emotion regulation strategies up to three months postintervention. Furthermore, patients improved regarding their self-efficacy, depressiveness, anxiety, and NSSI symptomatology. The developed DHI was described as a helpful and supportive tool. Conclusion: The intervention has shown initial evidence to be feasible and beneficial for adolescents conducting NSSI. The DHI has demonstrated to be a valuable tool in the treatment of self-harming youth.